Variabilidade espacial das perdas na colheita mecanizada do algodoeiro com diferentes armações de coleta - Da Silva, Rouverson Pereira [UNESP]; Cortez, Jorge Wilson; Voltarelli, Murilo Aparecido [UNESP]; Cassia, Marcelo Tufaile [UNESP]; Furlani, Carlos Eduardo Angeli [UNESP] (My University, 2013)
In any mechanized operation is the common occurrence of losses, and in the case of the harvest is important that these be quantified in order to minimize them. The work aimed was evaluated the influence of spatial quantitative losses (soil, plants and total) in operation mechanically harvested cotton, using frames with collection areas 1.125 m, 2.25 m and 4.50 m. Samples were collected in the municipality of Ipameri, GO, on a plot of 1.4 ha, being demarcated 41 points, spaced at 50 mx 9 m. The crop was harvested by a combine harvester John Deere, model 9960, with five lines platform. The samples were collected by placing the frame on the ground, collecting all cotton lying on the ground and then made up the collection that remained in the cotton plant after the passage of the harvester. Data were analyzed using descriptive statistics and geostatistics for making the maps. Losses had found large spatial variability, with high indices considered for the mechanical harvesting of cotton, predominantly losses on losses in plants in soil. The frame of 4.50 m showed the smallest variance and coefficient of variation than the frames of 1.125 and 2.25 m.
Spatial variability process of the losses in the mechanized harvesting of cotton with different frames collection
Keywords: Geostatistics; Precision farming; Sample areas